An Anova-Based Numerical Analysis of WHA Partial Replacement Concrete - Murugesh , V.; Santhosh , S.; N, Sneha; Unni, P. Manjula; Thangaraj, R.; Sadhasivam , M. (International Journal of Membrane Science and Technology, 2023)
In this work, a study exploiting concretes made with a bio-plant using natural waste is presented. The study examined the effects of partial cement substitution with bio-plants on the mechanical characteristics of conventional concretes and assessed the discrepancy between actual and expected elasticity modulus values. The usage of and effects on the modulus of elasticity of the partial replacement of concrete with WHA have been the subject of extensive research. Research was conducted in the area using various water-cement ratios coupled with water hyacinth ash and replacement percentages of cement. One-way analysis of variance (ANOVA) is used as a practical approach to verify normality. The supplied experimental data sets are used to train and evaluate the reliability predicting model. Thus, the study effort provides an overview of the numerical analysis performed using statistical techniques and the examination of the resulting data. The model’s dependability is provided by the linear relationship between the Concrete mix% and with & without WHA. The 90C+10%WHA mixture performs better than conventional concrete.